Functional gradation by differential thermo-mechanical treatment. (15th February 2010) - Weidig, U.; Saba, N.; Steinhoff, K.
For the production of bulk steel products with tailored properties, a new approach of thermo-mechanical processing offers a high potential of process innovations. The application of differential thermo-mechanical effects to initial homogeneous workpiece materials combines thermally-controlled material flow with functional grading of mechanical properties. The key effect is the control of local microstructural transformation. The detailed investigation and description of all related phenomena, not only for forming processes of bulk steel products but also for light metals and polymers is the main topic of the recently-established Transregional Collaborative Research Centre 30, which is financed by the German Research Foundation. Recent optimisations of the experimental setup in the field of hybrid metal forming offer new possibilities in the investigation of the main effects. The effects of different heating strategies are investigated through temperature and hardness measurements. Finite element simulations extend the range of the process monitoring. An appropriate choice of differential heating conditions and resulting thermo-mechanical effects creates a functional graded microstructural and resulting mechanical property distribution of bulk products.